Caribbean Report 25-08-1995 - Richards, Ken (anchor); Rappaport, Edward (interviewee); Meade, Reuben (interviewee); Crosskill, Hugh (correspondent); Burton, Anthony (interviewee); Chan, Michael Shree (interviewee); Ferdinand, Elizabeth (interviewee); Fraser, Tony (correspondent); Carrington, Edwin (interviewee); Rush, George (correspondent); Saul, David (interviewee) (The British Broadcasting Corporation, 1995)
In this report storm warnings are in effect on a number of islands in the Eastern Caribbean. Ed Rappaport from the Hurricane Centre in Miami comments on which range of islands are under threat. Meanwhile, Montserrat is a little more concerned about tropical storm Iris than the continuing threat of a volcanic eruption. Montserrat's Chief Minister Reuben Meade comments on the continuing exodus of residents as they flee a possible eruption. The Overseas Development Agency in Britain has sent Dr. Gilbert Greenall to Antigua to assist in the temporary resettlement of Montserratians. Two convicted murderers in Belize escaped execution after the Privy Council in London granted a stay of execution. The Guyana government has lashed out against Barbados' decision to ban all seafood from Guyana following the latest cyanide spill into the Essequibo River. Guyana's Trade, Tourism and Industry Minister Michael Shree Chan condemns Barbados' reaction but Barbados' Acting Chief Medical Officer, Elizabeth Ferdinand states it is merely a precautionary measure. CARICOM Secretary-General Edwin Carrington states there are some concerns relating to the funding of the Association of Caribbean States (ACS) Secretariat. Bermuda's new Premier is Dr. David Saul, the present Minister of Finance. In cricket, the final test between England and the West Indies could end up in a tame draw.
1. Headlines with Ken Richards (00:00-00:27)
2. A number of Caribbean islands on storm alert (00:28-02:49)
3. Montserrrat deals with its volcano threat while keeping an eye on tropical storm Iris (02:50-05:07)
4. The British government offers its support to Montserrat (05:08-06:03)
Keywords: Hurricanes -- Caribbean Area; Natural disasters -- Planning; Volcanoes -- Montserrat; Evacuation of civilians -- Montserrat; Emergency management -- Montserrat; Assistance in emergencies -- Great Britain; Economic assistance, British -- Antigua and Barbuda; Murderers -- Belize; Appellate procedure -- Belize; Appellate courts -- Belize; Seafood -- Safety measures; Seafood -- Contamination -- Guyana; Food imports -- Government policy -- Barbados; Regionalism (International organization); Caribbean Area -- Economic integration; Finance; Bermuda Islands -- Politics and government; Political leadership -- Bermuda Islands; Cricket -- West Indies; Cricket -- Tournaments -- England; Great Britain. Privy Council; Association of Caribbean States